2003
DOI: 10.1046/j.1365-2567.2003.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Costimulation through OX40 is crucial for induction of an alloreactive human T‐cell response

Abstract: SUMMARYThe alloreactive immune response is a series of events initiated by the interaction of T cells with allogeneic dendritic cells (DCs), involving alloantigen recognition and costimulatory signals. In this study, we investigated the role of OX40 in alloreactivity in vitro. We ®rst demonstrated that anti-OX40 ligand (anti-OX40L) monoclonal antibody (mAb) could markedly suppress the mixed leucocyte reaction (MLR) of peripheral blood mononuclear cells (PBMC). To further de®ne the contribution of the OX40/OX40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…However, we found only minimal expression of CD80, CD86, and CD40L on the surface of human MCs by FACS, and Fc⑀RI activation did not up-regulate the expression of these molecules (data not shown). Both OX40L and 4-1BBL can induce proliferation of T cells and differentiation from naive T cells to Th2 cells (18,20,26). Thus, we hypothesized that tonsillar MCs might induce the activation of T cells by interaction with OX40/ OX40L or 4-1BB/4-1BBL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found only minimal expression of CD80, CD86, and CD40L on the surface of human MCs by FACS, and Fc⑀RI activation did not up-regulate the expression of these molecules (data not shown). Both OX40L and 4-1BBL can induce proliferation of T cells and differentiation from naive T cells to Th2 cells (18,20,26). Thus, we hypothesized that tonsillar MCs might induce the activation of T cells by interaction with OX40/ OX40L or 4-1BB/4-1BBL.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases of costimulatory signaling, TNF superfamilies (TNFSFs) and TNF receptor superfamilies (TNFRSFs) critically regulate T celldependent immunity (16). OX40 ligand (OX40L) and 4-1BB ligand (4-1BBL), which are members of TNFSF, have been shown to transmit a costimulatory signal for T cell proliferation and cytokine production (17)(18)(19)(20)(21). Moreover, it has been reported that OX40L has the ability to induce the differentiation of naive CD4 ϩ T cells into Th2 cells producing IL-4 in vivo and in vitro (22)(23)(24)(25)(26).…”
Section: Ast Cells (Mcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…OX40 is expressed on activated CD4 ϩ T cells (22,23), whereas OX40L is induced on activated mouse CD11c ϩ DCs (24,25) and human monocyte-derived DCs (23,26). The stimuli triggered by OX40L on these DCs elicit a costimulatory role in preferential priming of Th2 cells (24,25,27).…”
Section: S Everal Lines Of Evidence Indicate That Plasmacytoid Cells mentioning
confidence: 99%
“…5). In addition, we examined the role of TCR-MHC interaction in the proinflammatory response by blocking activation of T cells using an anti-HLA-DR mAb (23). Thus, induction of proinflammatory cytokines requires Ag presentation on MHC class II molecules and is not a TCR-independent process.…”
Section: T Cells Require the Presence Of Apc To Express Proinflammatomentioning
confidence: 99%